Comparison of the effects of amitriptyline and flunarizine on weight gain and serum leptin, C peptide and insulin levels when used as migraine preventive treatment - Berilgen, MS; Bulut, S; Gonen, M; Tekatas, A; Dag, E; Mungen, B (Sage Publications Ltd, 2005)
The tricyclic antidepressant amitriptyline (AMT) and the calcium channel blocker flunarizine are frequently used in the preventive treatment of migraine, but the side-effect of prominent weight gain that frequently emerges during preventive treatment of migraine with these agents often leads to the discontinuation of therapy. In this study, we aimed to investigate the possible relationship between the weight gain associated with the use of these agents and serum levels of leptin, C-peptide and insulin in patient with migraine. Forty-nine migraine patients with a body mass index (BMI) < 25 and without any endocrinological, immunological or chronic diseases were randomly divided into two groups, receiving AMT or flunarizine. There was a statistically significant increase in serum levels of leptin, C-peptide, insulin and measures of BMI in both groups when measured at the 12th week of therapy compared to their respective basal levels. To our knowledge this is the first study investigating the effects of AMT and flunarizine on serum leptin levels in preventive use of migraine treatment. A result from this study indicates that AMT and flunarizine may cause leptin resistance possibly by different mechanisms and thereby result in increase in serum leptin levels and BMI.
Keywords: migraine; leptin; weight gain; flunarizine; amitriptyline